Pengaruh Metode Motor Educability terhadap Kemampuan Teknik Dasar Futsal pada Ekstrakurikuler di SMA Negeri 1 Anjatan - Titin Sri Lani; Bambang Ismaya; Fahrudin; Dira Fauzi (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to determine the effect of the application of the motor educability method on improving basic futsal technique skills in extracurricular activities of SMA Negeri 1 Anjatan students. The research method used a pre-experimental design with a one-group pretest-posttest design model on 32 students who participated in futsal extracurriculars. The research instrument used the Iowa Brace Test to measure motor educability and the FIFA standard test to measure basic futsal technique skills which include passing, ball control, dribbling, and shooting. The treatment program was carried out for 2 weeks with an intensity of 6 times per week and a duration of 90 minutes per session. Data were analyzed using a paired sample t-test with a significance level of α=0.05. The results showed a significant increase in all components of the basic futsal technique with a significance value of p<0.001. Total basic engineering skills increased by 31.17% from an average of 69.47 to 91.13. The highest increase occurred in dribbling (34.93%), followed by ball control (32.75%), shooting (31.11%), and passing (26.67%). The conclusion of this study shows that the motor educability method has a very significant influence on improving the basic futsal technique skills of high school students.